Development of a survey and worry score to evaluate physician burnout and wellness interventions during COVID-19 in the Rio Grande Valley: A pilot study - Victoria Jacobsen; Ericka A. Vazquez; Lauren Herrera; Ruth Escalera; Daniel Salinas; Bharathi S. Gadad; Juan Carlos Lopez-Alvarenga; Kelsey Potter-Baker (PLoS ONE, 2026)
Background Current research on physician burnout is limited in rural communities and physicians caring for the medically underserved. This study aimed to create an instrument to quantify the rate of physician burnout during the COVID-19 pandemic and identify effective coping interventions in an underserved mixed rural-urban region along the Texas–Mexico border. Methods We conducted a regional study in a sample of US physicians using a structured questionnaire developed by a multidisciplinary group. Thirty-one participants were contacted over a five-week period between December 2022 to January 2023. Participants self-selected based on their experiences of burnout during various phases of the COVID-19 pandemic (e.g., Initial Surge, Lock Down, Adjustment Period, Vaccine Distribution, Delta Variant, Booster Available). A 5-point Likert scale was used to assess and rank the perceived effectiveness of services employed to cope with burnout and its negative implications. Results We found that 43% of participants experienced burnout during the COVID-19 pandemic, with flexible schedules and personal wellness being the top alleviators of burnout. The survey showed good internal consistency and reliability (Cronbach’s alpha coefficient = 0.7680), McDonald’s omega was 0.80, and identified three “worry types” through latent factor analysis. Worry types included: (1) physicians with a desire to self-preserve but showed negative coping, (2) physicians with a desire for occupational harmony but with concerns about patient safety, and (3) physicians with concerns about personal safety and their mortality potential. Additionally, latent factor analysis showed that 9 questions from the survey could be used to create a Worry Score to classify burnout and coping strategies related to the COVID-19 pandemic. Conclusion These findings suggest that healthcare administrators and policymakers should prioritize implementing and promoting flexible work schedules and opportunities for personal time as part of comprehensive strategies to improve physician wellness and mitigate burnout. Additional research is needed to determine the effectiveness of the interventions in addressing physician burnout.